Специфика аргументации экспрессии в художественном тексте Characteristics of Intellectual Inference in the Expression in The Artistic Text (Journal of the College of Languages (JCL), 2018)
Аннотация В статье считается национально-культурная специфика и языковое изменчивость выражения заключений в художественном тексте. В настоящее время в изучении художественного текста существует множество взаимодополняющих подходов и концепций, которые способствуют лучшему пониманию его языковых и культурных аспектов. Художественный текст как «воспроизведение» и отражение реальности создает свою собственную систему корреляции слов, составных компонентов и частей различного содержания и различных структур. Кроме того, каждый известный писатель, как яркий представитель языкового сообщества, к которому он принадлежит, в форме искусства отражает характерные черты национального менталитета и особенности национального общения. Исходя из этого, мы рассматриваем литературный текст как лингвокультурное образование, являющееся носителем индивидуальности автора и общие этнокультурные характеристики коммуникативного поведения людей.Abstract This paper deals with the national-cultural characteristics of inference along with linguistic variation of expression in the artistic text. Presently, there exist many strategies and complementary conceptions in the study of artistic text, where all contribute to a better understanding of its lingua-cultural aspects. An artistic text is known as a "recovery" which creates a reflection of the nature of its own system for word association which make by itself the elements of the contents therein and of the various structures . As well, any well-known writer is an active representative of the language community to which he belongs and reflects in the form of art, the distinctive characteristics of the national intellect accompanied by the characteristics of national communication. Accordingly, we consider the literary text as a sort of language culture which bears the identity of the author and the general ethno-cultural characteristics of people's communicative behaviour.